The deevolution of concurrent logic programming languages - Tick, E. (The journal of logic programming, 1995)
This article surveys the field of implementation of concurrent logic programming languages. I briefly review language semantics and programming paradigms, before summarizing the results of the past decade in compiler and runtime system implementation. A theme throughout the research presented is the deevolution of concurrent logic programming languages due to the limitations of what systems designers and compiler writers can efficiently implement, as well as the growing perception among programmers that reduced expressivity is sufficient.